Cycles, Trends, Disruptions: Real Estate Centrality on the Global Financial Crisis, COVID-19 Pandemic, and New Techno-Economic Paradigm - Renan P. Almeida (Real Estate)
Real estate plays a pivotal role in the contemporary world, accounting for over half of global wealth and significant employment and GDP shares. This essay examines three key events—the 2007–2008 Global Financial Crisis (GFC), the COVID-19 pandemic, and recent technological revolutions—to place real estate’s centrality. By analyzing housing price indexes in major economies, the paper identifies global trends and regional nuances, as well as highlights real estate’s dual role as both a reflection and a driver of economic cycles. Then, I explore in detail the GFC, the urban roots of COVID-19 and its effects on real estate markets, and the relationship between new techno-economic paradigms and cities and real estate. Future research directions on real estate are also pointed out.